2015
DOI: 10.2903/j.efsa.2015.3998
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Flavouring Group Evaluation 86, Revision 2 (FGE.86Rev2): Consideration of aliphatic and arylalkyl amines and amides evaluated by JECFA (65th meeting)

Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to consider evaluations of flavouring substances assessed since 2000 by the Joint FAO/WHO Expert Committee on Food Additives (JECFA), and to decide whether further evaluation is necessary, as laid down in Commission Regulation (EC) No 1565/2000. The present consideration concerns a group of 30 aliphatic and arylalkyl amines and amides evaluated by JECFA at the 65 th meeting in 2005.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In its assessment of isolated piperine and several aliphatic and arylalkyl amines and amides as flavouring agents, the European Food Safety Authority EFSA (2015) reported an estimated European per capita intake of 6.2 µg piperine/day for the use of isolated piperine as a flavouring substance based on the EU Maximised Survey-derived Daily Intake (MSDI) method (see also below). However, EFSA noted in this assessment that the use levels were needed for some of the abovementioned flavouring substances, including piperine, to calculate the Modified Theoretical Added Maximum Daily Intakes (mTAMDIs) in order to identify those flavouring substances that required a more refined exposure assessment and to finalise the evaluation [32].…”
Section: Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In its assessment of isolated piperine and several aliphatic and arylalkyl amines and amides as flavouring agents, the European Food Safety Authority EFSA (2015) reported an estimated European per capita intake of 6.2 µg piperine/day for the use of isolated piperine as a flavouring substance based on the EU Maximised Survey-derived Daily Intake (MSDI) method (see also below). However, EFSA noted in this assessment that the use levels were needed for some of the abovementioned flavouring substances, including piperine, to calculate the Modified Theoretical Added Maximum Daily Intakes (mTAMDIs) in order to identify those flavouring substances that required a more refined exposure assessment and to finalise the evaluation [32].…”
Section: Exposurementioning
confidence: 99%
“…In its evaluations, EFSA (2008;2011;2015) disagreed with a No Observed Effect Level (NOEL) of 20 mg piperine/kg bw/day that had previously been identified by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) (2006), due to the shortcomings of the underlying animal study (lack of histopathology, study duration) and in 2015 identified a No Observed Adverse Effect Level (NOAEL) of 5 mg piperine/kg bw/day, based on a newly available 90-day rat feeding study performed according to OECD guideline 408 (endpoint: dose-dependent increase in cholesterol level in male animals) [29,32,[48][49][50] (see (2) in Section 4.2.2). In its final conclusion, EFSA (2015) agreed with the JECFA (2006) conclusion "no safety concern at estimated levels of intake as flavouring substance" based on the MSDI approach (estimated European per capita intake by the MSDI approach: 6.2 µg piperine/day) [32,50]. Currently, isolated piperine is approved as a flavouring agent in the European Union with no restrictions on use or maximum levels set in regulation (EC) No.…”
Section: Information Based On Evaluations By Scientific Bodies and National Authoritiesmentioning
confidence: 99%
“…Recently, the European Food Safety Authority (EFSA) identified the NOAEL of piperine, which is 5 mg/kg b.w. per day based on the most comprehensive study available (90-day dietary toxicity study in rats) [147].…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Although the dietary consumption of black pepper varies considerably within the population, EFSA calculated that the estimated exposure to piperine from natural sources when consuming black pepper as a flavoring ingredient is 6.2 µg/day in Europe and 0.07 µg/day in the USA, based on the maximized survey-derived daily intake [147], which are below the TTC threshold level of 1.5 µg/kg b.w./day (90 µg/day) for Cramer Class III compounds.…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Based on these data, and the fact that piperine is more irritant rather than toxic, its intake from regular food raised no safety concern. No observed adverse effect level (NOAEL) of piperine is 5 mg/kg daily [56].…”
Section: Toxicological Data On Piperinementioning
confidence: 99%